Retraction notice to “MPPT efficiency enhancement of a grid connected solar PV system using Finite Control set model predictive controller” [Heliyon 10 (2024) e27663] - Ayodeji Olalekan Salau; Girma Kassa Alitasb (Heliyon)
This article has been retracted: please see Elsevier policy on article withdrawal (https://www.elsevier.com/about/policies-and-standards/article-withdrawal).This article has been retracted at the request of the Editor-In-Chief.An investigation conducted on behalf of the journal by Elsevier's Research Integrity & Publishing Ethics team found a significant increase of citations to papers published by the author, Ayodeji Olalekan Salau, between the original submission and the revised version of this article. In summary, zero papers by the author were cited in the original version of the article. This increased to ten papers in the revised version of the article. The investigation also found phrases that make some passages in the article difficult to parse. The authors were requested to explain the use of these passages of text but were unable to do so. The Editor has lost confidence in the findings of the article and has determined that it should be retracted.The authors disagree with the retraction and dispute the grounds for it.